Synthesis, characterization and up-conversion luminescence properties of α-NaYF4:Yb3+/Er3+/PVP/MOFs multilayer nanocrystals - Thi Kieu Giang Lam; Lukasz Marciniak; Quang Huy Tran; Manh Tien Dinh; Duc Chinh Vu; Vu Nguyen; Thu Huong Tran; Thi Khuyen Hoang; Thanh Huong Nguyen; Duc Roan Pham; Thanh Binh Nguyen; Quoc Minh Le (Vietnam Journal of Science, Technology and Engineering, 2017)
The precursor PVP-capped α -NaYF4:Yb3+/Er3+ nanospheres were used as the templates for preparing the α -NaYF4:Yb3+/Er3+/PVP/MOFs multilayer nanocrystals with a self-template method. By using iron (III) carboxylate and zeolitic imidazolate frameworks dissolved in dimethylformamide (DMF) solution containing 25% of diethylene glycol (DEG), the sphericalshaped α -NaYF4:Yb3+/Er3+/PVP/MIL-100 and α-NaYF4:Yb3+/Er3+/PVP/ ZIF-8 multilayer nanocrystals were successfully prepared with the sizes of 300-500 nm at 100oC for one hour. Under a 976 nm laser excitation at room temperature, the α -NaYF4:Yb3+/Er3+/PVP/MIL-100 and α-NaYF4:Yb3+/ Er3+/PVP/ZIF-8 multilayer nanocrystals exhibited strong up-conversion luminescence with three emission bands centered at around 520 nm, 540 nm, and 655 nm corresponding to 2H11/2 → 4I15/2, 4S3/2 → 4I15/2, and 4F9/2 → 4I15/2 transitions of Er3+ ions, respectively.